Recruitment and Job-Seeking Mechanisms for Zimbabwean Women Care Workers in the Domestic Services Sector in South Africa - Baison, Precious (African Human Mobility Review, 2021)
This article explores the migration of Zimbabwean women to South Africa to undertake various types of care work within the broader domestic work sector. Studies on care migration have largely discussed South to North migration flows. This is despite evidence showing that there are significant flows of migrants within countries in the Global South. This article seeks to understand the recruitment and job-seeking strategies employed by women in this South-South migration flow in light of their migrant status and processes related to their migration. It is based on a qualitative study and utilizes data collected through semi-structured interviews conducted with key informants from four domestic worker recruitment agencies and 23 care workers in two cities – Johannesburg and Pretoria. The leading findings were that Zimbabwean migrant care workers in South Africa faced exploitative working conditions as the majority of them were undocumented or irregular. They faced challenges in obtaining valid work visas and therefore, migrant care workers could not seek employment through formal channels such as recruitment agencies. They used informal channels such as social networks and the ‘market’. The article discusses the implications of using such strategies with regards to the subsequent working conditions and the protection of care workers’ rights.